Randomized text encryption: a new dimension in cryptography - Memon, Jamshed; Abd Rozan, Mohd Zaidi; Uddin, Mueen; Abubakar, Adamu; Chiroma, Haruna; Daud, Dzurllkanian (Praise Worthy Prize S.r.l., 2014)
Cryptography refers to protecting transmitted information from unauthorized interception or tampering, while cryptanalysis is art of breaking such secret ciphers and reading information, or perhaps replacing it with different information. The research highlights a new encryption technique called randomized text encryption. The algorithm proposed increases the complexity of cryptanalyst to decrypt the ciphertext and restricts them to break the security of encoded file. The proposed technique uses random numbers added to plaintext along with encryption key. After applying encryption technique, each time same plaintext will be converted to different ciphertext provided that encryption key is same or different. Two different characters are generated against single character of plaintext that doubles the size of encrypted text. Decryption process doesn’t require random numbers but only needs encryption key to decipher the encrypted text. Consequently, the proposed technique is safe to different cryptanalytic attacks like Frequency analysis, Brute-Force, Linear and Differential Cryptanalysis.